Analisis Wacana Kritis Teun A Van Dijk Pidato Ketua DPR RI pada Sidang Tahunan MPR dan Sidang bersama DPR dan DPD Tahun 2024 - Setiowati, Rahayu; Mega, Ria Nur; Hutapea, Edison Bonartua (FISIP Universitas Bung Karno, 2025)
This study examines the speech of the Speaker of the Indonesian House of Representatives (DPR), Puan Maharani, delivered at the annual session of the People's Consultative Assembly (MPR) and the Joint Session of the DPR and the Regional Representative Council (DPD) in 2024. The study analyses Puan Maharani’s speech text structure, social cognition, and social dimensions. This qualitative study uses the critical discourse analysis approach Teun A. van Dijk developed. The study concludes, first, in terms of text structure, the Speaker of the DPR, Puan Maharani, uses positive vocabulary, inclusive metaphors, and polarization to strengthen the image of the DPR institution. Second, regarding social cognition, the speech of the Speaker of the DPR, Puan Maharani, is influenced by a pro-status quo ideology, with cognitive representations that benefit the dominant group. Third, in terms of social context, the speech of the Speaker of the DPR, Puan Maharani, aims to maintain the legitimacy of the DPR within the power structure, especially in crucial political or economic situations.Keywords: Critical Discourse Analysis, Speech, Text Analysis, Social Cognition, Social Context.